Retreatment in Congenital Syphilis Following Serologic Titer Elevation - Tabile Casanova, Julia; Caroline Sabóia de Souza Caria, Anne; da Silva Galina, Nicole; Alencar Mariot, Gabrielle; Eduarda Pinheiro Nogueira, Maria; Condor Loureiro da Silva, Ingrid; Gomes Cosendei, Victoria; Souza Queiroz, Thiago; dos Santos Bezerra, Yuri; Maciel Martins, Juliana; Pinto de Lima, Tainá; Henrique Lima Bittencourt, João; et al. (Brazilian Journal of Implantology and Health Sciences, 2026)
Congenital syphilis results from transplacental transmission of Treponema pallidum in pregnant women with active infection and remains a significant public health concern. Although it is a potentially curable condition, it requires systematic clinical and serological follow-up, including serial monitoring of non-treponemal tests such as the Venereal Disease Research Laboratory (VDRL) test to assess therapeutic response. We report the case of an infant with confirmed congenital syphilis who, despite receiving guideline-recommended treatment, exhibited a subsequent rise in non-treponemal titers during outpatient follow-up. This case raises important considerations regarding the interpretation of post-treatment serologic dynamics and the potential determinants of titer elevation, including therapeutic failure, reinfection, or atypical serologic response, thereby underscoring the need for rigorous longitudinal surveillance in exposed children.